2007
DOI: 10.1007/s00535-006-1998-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α-linolenic acid on colonic secretion in rats with experimental colitis

Abstract: Our results suggest that supplementation with alpha-linolenic acid, in combination with a lipoxygenase inhibitor, could suppress the increase in Cl- secretion in patients with UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In animal models, the PSO supplementation was found to decrease the level of arachidonic acid yet increase the level of ALA, eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) in the colon. The combination of PSO with lipoxygenase inhibitor suppresses the increase of chloride ion secretion-related diarrhea in mice’s colitis ( 20 ). Furthermore, the advantage of PSO is that it is inexpensive, free of heavy metal contamination, and safe ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In animal models, the PSO supplementation was found to decrease the level of arachidonic acid yet increase the level of ALA, eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) in the colon. The combination of PSO with lipoxygenase inhibitor suppresses the increase of chloride ion secretion-related diarrhea in mice’s colitis ( 20 ). Furthermore, the advantage of PSO is that it is inexpensive, free of heavy metal contamination, and safe ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence for the involvement of the 5-LOX pathway and COX-2 in the DSS model of colitis [ 9 , 11 , 12 , 13 , 30 , 31 ]. A recent study reported the measurement of lipid inflammatory mediators throughout the different phases of inflammation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a DSS study using a LOX inhibitor (AA-861) and linolenic acid supplementation, the combination was able to suppress the excessive chloride secretion that results in diarrhea. Linolenic acid is metabolized to the anti-inflammatory eicosanoids PGE1 and TBA1 and prevents the formation of leukotrienes, while AA-861 is a selective 5-LOX and LTB4 inhibitor [ 13 ]. In another study, DSS caused a marked inflammatory response in the colon and a subsequent 5-fold increase in eicosanoid production [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that ALA has a strong effect on reducing risks of chronic diseases such as atherosclerosis, thrombosis and hyperlipidemia (Rodriguez-Leyva et al, 2010;Zhao et al, 2004;Winnik et al, 2011). Recently, dietary supplementation with ALA has been shown to improve colonic inflammation of experimental colitis rats (Shimizu et al, 2007;Wen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%